Get expert advice and insights on any topic with IDNLearn.com. Our experts provide prompt and accurate answers to help you make informed decisions on any topic.
Sagot :
Certainly! Let's evaluate the function [tex]\( F(x) = 2x^3 - x^2 - 4x + 9 \)[/tex] for [tex]\( x = 3 \)[/tex].
1. First, substitute [tex]\( x = 3 \)[/tex] into the function [tex]\( F(x) \)[/tex].
[tex]\[ F(3) = 2(3)^3 - (3)^2 - 4(3) + 9 \][/tex]
2. Next, calculate each term individually:
- [tex]\( (3)^3 = 27 \)[/tex]
- So, [tex]\( 2(3)^3 = 2 \cdot 27 = 54 \)[/tex]
- [tex]\( (3)^2 = 9 \)[/tex]
- Thus, [tex]\( - (3)^2 = - 9 \)[/tex]
- Then, [tex]\( 4(3) = 12 \)[/tex]
3. Now, combine all the terms:
[tex]\[ F(3) = 54 - 9 - 12 + 9 \][/tex]
4. Finally, perform the arithmetic operations:
[tex]\[ 54 - 9 = 45 \][/tex]
[tex]\[ 45 - 12 = 33 \][/tex]
[tex]\[ 33 + 9 = 42 \][/tex]
So, the value of [tex]\( F(3) \)[/tex] is 42. Therefore, the correct answer is:
D. 42
1. First, substitute [tex]\( x = 3 \)[/tex] into the function [tex]\( F(x) \)[/tex].
[tex]\[ F(3) = 2(3)^3 - (3)^2 - 4(3) + 9 \][/tex]
2. Next, calculate each term individually:
- [tex]\( (3)^3 = 27 \)[/tex]
- So, [tex]\( 2(3)^3 = 2 \cdot 27 = 54 \)[/tex]
- [tex]\( (3)^2 = 9 \)[/tex]
- Thus, [tex]\( - (3)^2 = - 9 \)[/tex]
- Then, [tex]\( 4(3) = 12 \)[/tex]
3. Now, combine all the terms:
[tex]\[ F(3) = 54 - 9 - 12 + 9 \][/tex]
4. Finally, perform the arithmetic operations:
[tex]\[ 54 - 9 = 45 \][/tex]
[tex]\[ 45 - 12 = 33 \][/tex]
[tex]\[ 33 + 9 = 42 \][/tex]
So, the value of [tex]\( F(3) \)[/tex] is 42. Therefore, the correct answer is:
D. 42
We appreciate your contributions to this forum. Don't forget to check back for the latest answers. Keep asking, answering, and sharing useful information. Thank you for visiting IDNLearn.com. We’re here to provide accurate and reliable answers, so visit us again soon.